Analisis kepuasan taruna akademi kepolisian terhadap layanan pendidikan dan pembinaan tahun 2025: pendekatan mixed methods - Susy Fitria; Monica Niken Wulandari; Sahrul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The implementation of educational and developmental services constitutes a systematic effort to put policies, programs, and academic activities into practice in order to meet cadets’ needs and enhance their satisfaction. This study aims to analyze the satisfaction level of the Police Academy cadets with the implementation of educational and developmental services in 2025. The research employs a mixed-methods approach with a sequential explanatory design, in which quantitative data are collected and analyzed first, followed by qualitative data to further explain the quantitative findings. Quantitative data were obtained through a five-point Likert-scale questionnaire ranging from “very satisfied” to “very dissatisfied.” The questionnaire was distributed to Police Academy cadets, while qualitative data were collected through interviews and observations. Quantitative data were analyzed descriptively to determine cadet satisfaction levels, whereas qualitative data were analyzed through data reduction, data display, and conclusion drawing. The quantitative results indicate that respondents’ satisfaction falls within the “Very High” category, with an average score of 91.6%. Qualitative findings further show that, in general, cadets hold positive views regarding the implementation of academic and non-academic activities within the educational environment. However, several aspects still require improvement, including the utilization of learning technologies, active instructor engagement, and the availability of supporting facilities and infrastructure.